(untitled) (gjstudies, 2025)
This research investigates the complex relationship between discretionary accounting policy choices and income smoothing behavior, moving beyond traditional agency theory frameworks to propose a novel, multi-dimensional model ofmanagerial signaling. While prior literature predominantly views income smoothing as opportunistic earnings management aimed at misleading stakeholders, weconceptualize it as a heterogeneous phenomenon that can also serve as a crediblecommunication mechanism under specific governance conditions. Our methodology employs a unique, two-stage analytical framework combining computationallinguistics analysis of financial statement narratives with a machine learning classification of policy choice clusters. We analyze a comprehensive, hand-collecteddataset of 1,250 U.S. firms from 2015 to 2023, focusing on discretionary choicesin revenue recognition, depreciation methods, inventory valuation, and provisionestimations. The first stage utilizes natural language processing to extract andquantify the explicitness and consistency of policy justifications in managementdiscussion and analysis (MDA) sections. The second stage applies an unsupervised learning algorithm to identify distinct firm archetypes based on their policychoice portfolios and smoothing outcomes. Our results reveal three distinct behavioral clusters: ’Opaque Smoothors’ exhibiting high smoothing with low justificationclarity, associated with weaker governance; ’Transparent Communicators’ demonstrating moderate, stable smoothing paired with high narrative clarity, linked tosuperior long-term performance; and ’Policy Volatiles’ showing erratic choices andlow smoothing, correlated with strategic uncertainty. Crucially, we find that themarket penalizes opaque smoothing but rewards transparent smoothing, indicating that investors differentiate between opportunistic and communicative behavior.Furthermore, we document that the efficacy of policy-based smoothing as a signalis contingent on the firm’s information environment quality and audit committeefinancial expertise. This study contributes original insights by reframing incomesmoothing within a signaling theory paradigm, demonstrating that accounting policy choices constitute a nuanced language through which managers convey privateinformation about future cash flow stability, and by providing a new methodologi1cal lens to disentangle the multifaceted drivers of this pervasive financial reportingpractice